Visual Branding Design Review of Local Coffee Store in Jakarta - Novena Ulita (Green Publisher Indonesia, 2022)
The Indonesian government's campaign that invites to love local coffee products also strengthens the habit of drinking coffee as a contemporary lifestyle. This has resulted in encouraging the emergence of local coffee shop product brands in Jakarta that compete with non-local brand coffee shops which have a lot of demand first. This competition eventually triggers the creativity of producers in creating a brand identity as part of the power of product marketing. This research uses a qualitative method with a netnographic approach and a case study. The research uses a netnographic method related to the existence of local coffee shops on digital artifacts that are accessed online. Using the theory of visual branding and brand identity, this study aims to find trends and big ideas for local coffee shop branding visual design ideas from 2015-2018 in Jakarta as part of the image of Indonesian local brand identity. The results of this study conclude that overall the visual elements used to describe marketing strategies with big ideas are keywords that are different from each other by describing their respective advantages. The dominant color used by the eight samples of visual branding also supports the big idea of ​​professional, classic, modern, locality, ethnic, cultural, and romantic keywords that build these emotions in consumers. This has finally become a trend for the development of visual branding for local coffee shops in Jakarta.